The petenes of Sian Ka'an, Quintana Roo and their relationship with water pressure gradients - López-Portillo, Jorge; Ezcurra, Exequiel; Maass, José Manuel (Instituto de Ecología, A.C., 1989)
Ist has been suggested tha hummocks (petenes), present in karstic areas, are fed with fresh, continental water from underground sources. We tested this supposition. Three humocks and their associated inmersed areas were chosen around the Chunyaxché Lagoon, and soil samples from edaphic horizons and samples from the phreatic water were taken. Samples from continental and sea water were also taken.In water and soil samples, pH and concentration of four cations were determined in soils. A multivariate analysis of variance (MANOVA) made on the variables measured in soils showed no significant differences between the hummocks and their associated inmersed zones differ more from continental areas that between them. These result suggests that a direct continental  water source is not necessary to determine the presence of a hummonck. Thus, hummoncks could be considered as islets which are occupied by tropical evergreen seasonal forest and/or magrove species, according to the flooding condition in the islet.